Legal Liability Of Inadvertent Customs Documents By Customs In Export Business - Ayun, Qurrota; Hapsari, Dwi Ratna Indri (Simbur Cahaya, 2024)
The purpose of this study is to investigate the legal consequences that exporters may face when an unintentional error occurs in customs clearance procedures carried out by the Customs. This research applies the normative juridical research method to analyze the legal liability of the Customs in the case of inadvertent customs documents, focusing on the provisions stipulated in PMK 274/PMK.04/2014. Data collection is done through a literature study using primary legal sources, especially related laws and regulations. Data were classified and analyzed normatively to understand the implementation and impact of Customs' legal liability. The results of the study provide an overview of the export duty restitution mechanism and aspects of the legal liability of Customs, focusing on export cancellation, overpayment, and the role of the Tax Court. This research is expected to contribute to a deeper understanding of the customs legal framework in Indonesia and can serve as a reference for relevant stakeholders.